1998
DOI: 10.1089/dna.1998.17.859
|View full text |Cite
|
Sign up to set email alerts
|

Gene and cDNA Structures of Flounder Insulin-Like Growth Factor-I (IGF-I): Multiple mRNA Species Encode a Single Short Mature IGF-I

Abstract: To understand the comprehensive mechanisms of gene expression and processing for insulin-like growth factor-I (IGF-I) in vertebrates, we have investigated the gene organization, promoter and transcriptional initiation sites, alternative splicing and polyadenylating sites, and the cDNA structures of this gene in the Japanese flounder, Paralichthys olivaceus. The flounder IGF-I gene was found to be composed of five exons and four introns spanning 17.5 kb. By Northern blot analysis, two major mRNA classes of 4.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The utilizing of an alternative 5 0 splice site resulted in the deletion of an 81-nt region encoding 27 residues of the E domain. The identified perch IGF-Ia and IGF-Ib correspond to the two IGF-I transcripts isolated from Japanese flounder (Tanaka et al 1998) and barramundi (Lates calcarifer) (Sta˚hlbom et al 1999). Correspondingly, two alternative spliced transcripts were also identified in each of the duplicated IGF-I genes in salmonids (Wallis and Devlin 1993;Duan et al 1994;Duguay et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilizing of an alternative 5 0 splice site resulted in the deletion of an 81-nt region encoding 27 residues of the E domain. The identified perch IGF-Ia and IGF-Ib correspond to the two IGF-I transcripts isolated from Japanese flounder (Tanaka et al 1998) and barramundi (Lates calcarifer) (Sta˚hlbom et al 1999). Correspondingly, two alternative spliced transcripts were also identified in each of the duplicated IGF-I genes in salmonids (Wallis and Devlin 1993;Duan et al 1994;Duguay et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple long IGF-I transcripts have previously been identified in human and several fish species by Northern blot (Cao et al 1989;Sussenbach et al 1992;Lund 1994;Schmid et al 1999;Sta˚hlbom et al 1999). In Japanese flounder, two large IGF-I cDNA of 4691 and 2877 nt with different sized 3 0 UTR were isolated (Tanaka et al 1998) that corresponds to the 4.9 and 3.0 kb perch IGF-I transcripts identified by Northern blot analysis. Even the shortest transcript of about 1.5 kb is considerable longer than the isolated IGF-I cDNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…1 legend), these four receptors may be the products of four different genes. On the other hand, molecules of insulin (Andoh & Nagasawa 1998) and IGF-I (Tanaka et al 1998) have been reported to be produced by a single gene in Japanese flounder. The amino acid sequences of fIR-1 and fIR-2 are more homologous to that of human IR than to that of human IGF-IR, and those of fIGF-IR-1 and fIGF-IR-2 are more similar to that of human IGF-IR than human IR.…”
Section: Discussionmentioning
confidence: 99%
“…An RNase protection assay was performed by the previously described method (Tanaka et al 1998). Briefly, Figure 1 The nucleotide sequence of the flounder GHR gene.…”
Section: Rnase Protection Assaymentioning
confidence: 99%